Equivalent improvement in strength following high intensity, low and high volume training - Starkey, D. B.; Welsch, M. A.; Pollock, M. L.; Graves, J. E.; Brechue, W. F.; Ishida, Y. (Medicine & Science in Sports & Exercise, 1994)
Either one or three sets of high intensity strength training was performed, 3 days/wk for 14 weeks. It was found that one set (8-12 repetitions) was as effective as three. The superfluous training time might be used better for other activities. Implication: The stimulus for high intensity strength training does not have to include much volume. One maximal set is sufficient.